JOAO WANDERLEY GERALDI: THE LINGUIST RESEARCHER, TRAINING TEACHER AND UNIQUE BRAZILIAN READER OF BAKHTIN AND HIS STUDY CIRCLE - Giovani, Fabiana; Camargos, Moacir Lopes de (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2024)
This article aims to honor and discuss our meeting with Joao Wanderley Geraldi, the linguist researcher, teacher trainer and unique reader of Bakhtin and his Study circle. Our subject matter in this paper is the meetings we held with the author in his research and teaching activities throughout his years of activism, and in specially during the Linguistics V program taken at Unicamp in 2005. From mediations with Geraldi on language studies, we chose to share our understanding of speech genres - involving life and education - that converge around this construction. Finally, we show how this knowledge guides us to maintain the inseparable relationship between language and literature in dialogue through a poem by Manoel de Barros, a poet who was also introduced to us by Geraldi.
Keywords: Joao Wanderley Geraldi; Bakhtinian studies; meeting; speech genres